Le matin des sociologues. Entretien avec Alain Touraine - Michel-Antoine Burnier (Genre, Sexualité et Société)
We’re publishing here the interview that Alain Touraine gave to the magazine "Actuel" in 1972. He goes back over the student protest movements of May 1968 and the new emerging social problematisations, among which sexuality. He especially insists on the modalities by which the balances of power establish themselves in post-industrial societies and on the conditions of production in social action. And therefore on the conditions of the emergence of a sociologic reasoning. This is how the editors of Actuel presented the interview: "Alain Touraine was sociology professor at the University of Nanterre in 1968. He saw close up, around his student Cohn-Bendit, the birth and the gush of the movement we all know. As he had devoted his studies to the analyses of the workers' consciousness and to industrial work, he refused to reduce the students' revolt and the protests to an intellectual and middle-class burst of energy or to the vicarious regeneration of a traditional proletariat shaking off the reformist yoke. The movement was much wider and different. Technicians, young workers, college and high-school students rose up against the grips of the big technocratic systems: the old discourses had to be affected by it and a new sociology could be born. Touraine will try to do so in "La société post-industrielle" (Denoël-Gonthier, Médiations, 7,80 F), "Le communisme utopique" (now out in pocket-book, Le Seuil, Politique) and in his latest book (also at Le Seuil) "Université et société aux Etats-Unis".